2017
DOI: 10.1177/1535370217725249
|View full text |Cite
|
Sign up to set email alerts
|

Hydrogen-rich saline inhibits tobacco smoke-induced chronic obstructive pulmonary disease by alleviating airway inflammation and mucus hypersecretion in rats

Abstract: This study was designed to evaluate protective effect of hydrogen-rich saline, a novel antioxidant, on tobacco smoke (TS)-induced chronic obstructive pulmonary disease (COPD) in rats and explore the underlying mechanism. Our results suggest that administration of hydrogen-rich saline improves lung function and alleviates morphological impairments of lung through alleviating inflammation, reducing oxidative stress and lessening mucus hypersecretion in TS-induced COPD rats. AbstractChronic obstructive pulmonary … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
9
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(10 citation statements)
references
References 39 publications
(49 reference statements)
1
9
0
Order By: Relevance
“…The proteins AQPs not only control the volume of liquid secreted to the airway cavity but also impact the expressions of mucin [30]. Similar to previous study, we also found decreases of AQPs and increases of mucin protein in COPD rats' lung [31]. However, although no difference was found between COPD and CDSCOPD rats, we cannot exclude the possibility that longer time of cold-dryness stimulation might impact expressions of AQPs and mucins in lung.…”
Section: Discussionsupporting
confidence: 74%
“…The proteins AQPs not only control the volume of liquid secreted to the airway cavity but also impact the expressions of mucin [30]. Similar to previous study, we also found decreases of AQPs and increases of mucin protein in COPD rats' lung [31]. However, although no difference was found between COPD and CDSCOPD rats, we cannot exclude the possibility that longer time of cold-dryness stimulation might impact expressions of AQPs and mucins in lung.…”
Section: Discussionsupporting
confidence: 74%
“…Hydrogen also has the potential to protect lung tissues from pulmonary hypertension [ 72 ], sepsis [ 73 ], smoke inhalation injury [ 74 ], hemorrhagic shock and resuscitation [ 75 ], and other toxic substances/events. In animal models, hydrogen also affects asthma and chronic obstructive pulmonary disease [ 76 ].…”
Section: Preventive and Therapeutic Applications Of H 2 mentioning
confidence: 99%
“…Hydrogen as a reducing agent has therapeutic effects for the reduction of oxidative stress, inflammation, and apoptosis (Xie et al, 2012; Xin et al, 2014; Shao et al, 2016; Lin et al, 2017). For example, hydrogen improves oxidant stress-induced organic injury, including acute kidney injury (Du et al, 2016), acute hepatic failure (Sun et al, 2011), chronic obstructive pulmonary disease (Liu Z. et al, 2017), and spinal cord injury (Ge et al, 2017) in rodents. Moreover, it can delay the progress of some diseases, such as diabetes and hypertension (Takeuchi et al, 2015; Guo et al, 2017).…”
Section: Introductionmentioning
confidence: 99%